The vulnerability of the visually impaired to HIV and AIDS : a study of the HIV and AIDS outreach efforts for visually impaired people - Booi, Nokuphumla (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.